الإعداد الثقافي للمعلم لمواجهة تحديات مجتمع المعرفة: رؤية مقترحة - ندا، عبدالرحمن أحمد Nada, Abdulrahman Ahmed (الأكاديمية العربية للعلوم الإنسانية والتطبيقية, 2017)
يشهد المجتمع العالمي المعاصر تغيرات علمية وتكنولوجية واجتماعية متسارعة، والتي من أهمها تحول الإنسانية من عصر الصناعة أو الحداثة إلى عصر جديد له مسميات مختلفة أشهرها عصر المعلومات، عصر التكنولوجيا، عصر المعرفة، ولقد اتفقت هذه المسميات جميعها على أن العصر الجديد سوف يشهد تغيراً شاملاً في طبيعة المعرفة وفي جميع مناشط الحياة. ولقد أدت التحولات المتسارعة التي يشهدها العالم في مختلف المجالات إلى تغيرات في غايات التربية وفي أهدافها، وإلى تحولات في دور المعلم الذي أصبح موجهًا ومنشطًا أكثر من كونه ملقنًا للمعرفة. فوفق هذه التحولات تحول دور المعلم إلى مرشد إلى مصادر المعرفة والتعلم، ومنسق لعمليات التعلم ومصحح لأخطاء التعلم، ومقوم لنتائج التعلم، وموجه إلى ما يناسب قدرات كل متعلم وميوله. وهي تستلزم معلمًا من طراز جديد، وإعدادًا للمعلم ملائمًا للأهداف المحدثة، وتدريبًا مستمرًا له على المعارف التربوية المتطورة. وفي ضوء الاعتبارات السابقة، وفي ظل التحديات الثقافية التي فرضها مجتمع المعرفة فإن هذا يحتم ضرورة الاهتمام ببرامج الإعداد الثقافي للمعلم سواء (قبل/ أو أثناء) الخدمة، لمواجهة تحديات مجتمع المعرفة. ويهدف البحث إلى تقديم رؤية مقترحة للإعداد الثقافي للمعلم لمواجهة تحديات مجتمع المعرفة، وسوف يتناول البحث الموضوع وفقاً للمباحث الآتية: - المبحث الأول: مجتمع المعرفة (المفهوم – السمات –الإشكاليات والتحديات). - المبحث الثاني: الإعداد الثقافي للمعلم (المفهوم-الأهمية-الأهداف-الواقع). - المبحث الثالث:تطوير الإعداد الثقافي للمعلم لمواجهة تحديات مجتمع المعرفة (المتطلبات-المقومات). - الخاتمة: (النتائج-التوصيات-المقترحات). The contemporary world community is witnessing rapid scientific, technological and social changes, the most important of which is the transformation of humanity from the age of industry or modernity to a new era with various names, most notably the information age, the age of technology and the age of knowledge. The nature of knowledge and in all aspects of life. The rapid transformations witnessed by the world in various fields have led to changes in the goals and aims of education, and to transformations in the role of the teacher, who has become more directed and active than our teacher of knowledge. With these transformations, the role of the teacher becomes a guide to knowledge and learning, a coordinator of learning processes, a corrector of learning errors, a learner of learning outcomes, and oriented to the abilities and dispositions of each learner. It requires a teacher of a new model, a teacher-friendly preparation of updated objectives, and continuous training on advanced educational knowledge. In the light of previous considerations, and in light of the cultural challenges imposed by the knowledge society, it is imperative to pay attention to the cultural preparation programs of the teacher, both before and during the service, to meet the challenges of the knowledge society. The research aims to provide a proposed vision for the cultural preparation of the teacher to meet the challenges of the knowledge society. The research will address the topic according to the following investigations: - The first topic: the knowledge society (concept - features - problems and challenges). - The second topic: the cultural preparation of the teacher (concept - importance - goals - reality). - The third topic: developing the cultural preparation of the teacher to meet the challenges of the knowledge society (requirements - constituents). - Conclusion: (Results - Recommendations - Proposals).
Keywords: مجتمع المعرفة -- التأهيل الثقافي -- الثقافة المعرفية -- التنمية المستدامة -- المعلمون